Mechanical properties of composite materials - Cheng, Bryan Yi Shen (2017)
The aim of the project is to develop a computational model using ABAQUS and analyse unidirectional fibre reinforced composites (GFRP). The model will be subjected to transverse uniform stresses and 2D analysis of model will be performed to determine the effects of volume fraction, fibre radius size and ratio of fibre modulus to matrix modulus. Literature review provides the necessary information in performing the study which includes a basic introduction of composites and existing theoretical models used for comparison. More importantly, the literature review also covers finite element analysis which provides the relevant properties and parameters used in the study. The generation of the computational model was supplemented by using PYTHON which allowed the auto generation of the models. The models were subjected to a uniform tensile stress in the transverse direction. For each variable, the simulations were performed numerous times where the average of the results were extracted. The results were calculated and translated into transverse effective moduli. The effects of volume fraction demonstrated a good agreement with the theoretical models. In terms of fibre radius, no conclusive evidence was produced to come to a conclusion. For fibre/matrix modulus ratio, it was found that a ratio 14 was found to be optimal and further increment of the ratio showed no significant improvement. Further works could focus on investigating other factors that may affect the properties of composites. By considering defects and interface’s bond strength, a more comprehensive simulation could be produced which will further enhance the accuracy of the simulations.